Altering interfacial properties through the integration of C60 into ZnO ceramic via cold sintering process. (30th April 2022) - Guo, Jing; Si, Mingming; Zhao, Xuetong; Wang, Li; Wang, Ke; Hao, Jianyu; Wang, Hong; Randall, Clive A.
Abstract: A lot of nanocomposites containing C60 have been developed to enable various application opportunities. However, it seems impossible to incorporate C60 into ceramics without destroying the C60 molecules, because ceramics are typically sintered at high temperatures that could result in the chemical reaction of C60 . Herein, we report the successful integration of C60 with ZnO using cold sintering process. (1-x)ZnO-xC60 composites with x ranging from 0 to 5 wt% are densified into monolithic structures with relative densities over 95%. Clear C60 molecules are observed in the cold sintered composites, and thin C60 layers with less than 10 nm are located at the ZnO grain boundaries. With C60 altering the interfacial structures of ZnO ceramics, the electrical properties are improved significantly, especially, the breakdown electric field at 1 mA cm −2 is enhanced from ∼80 V mm −1 to ∼2100 V mm −1 . The FEM analysis indicates that the current density at the interfaces of ZnO and C60 is higher than other regions. This work thus indicates that cold sintering process provides a promising pathway to design new types of functional materials through the integration of C60 and ceramics. Graphical abstract: Image 1